Integration of Digital Payment and E-Commerce as a Market Expansion Strategy for Culinary MSMEs - Sinaga, Kalvin; Saragih, Roy Sahputra; Siregar, Victor Marudut Mulia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study examines the adoption of digital payment systems and e-commerce platforms as strategic instruments for market expansion among culinary MSMEs in Pematangsiantar City. Despite the rapid progression of digital transformation in Indonesia, the utilisation of these technologies among MSMEs in medium-sized cities remains limited due to inadequate digital literacy, insufficient infrastructure, and low managerial readiness. Employing a quantitative approach through Partial Least Squares–Structural Equation Modelling (PLS-SEM) with a sample of 100 respondents, this study investigates the influence of digital payment and e-commerce adoption on market expansion strategies. The findings reveal that digital payment significantly enhances market expansion (β = 0.193; p < 0.05), indicating that efficient, secure, and reliable transaction mechanisms strengthen customer reach and business scalability. Conversely, e-commerce adoption does not demonstrate a significant independent effect (β = 0.127; p > 0.05), suggesting that its effectiveness is contingent upon stronger digital competencies and ecosystem support. However, the interaction between digital payment and e-commerce exhibits a significant synergistic effect (β = 0.158; p < 0.05), implying that integrated adoption yields greater strategic value than isolated implementation. With an explanatory power of 5.7%, the model also highlights the presence of other external factors influencing market expansion. Overall, this study contributes theoretical and practical insights into MSME digitalisation in non-metropolitan contexts and offers implications for policymakers and business support institutions in strengthening digital transformation initiatives.